2015
DOI: 10.1165/rcmb.2014-0391oc
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Conferred Enhanced Cellular Resistance against Bacterial Pore-Forming Toxins in Airway Epithelial Cells

Abstract: Statins are widely used to prevent cardiovascular disease. In addition to their inhibitory effects on cholesterol synthesis, statins have beneficial effects in patients with sepsis and pneumonia, although molecular mechanisms have mostly remained unclear. Using human airway epithelial cells as a proper in vitro model, we show that prior exposure to physiological nanomolar serum concentrations of simvastatin (ranging from 10-1,000 nM) confers significant cellular resistance to the cytotoxicity of pneumolysin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 62 publications
4
56
1
Order By: Relevance
“…In contrast, neither simvastatin nor TSA increased expression of LL‐37/hCAP‐18 in A549 cells investigated in our study. Statt et al observed a mevalonate‐dependent induction of CAMP gene expression by simvastatin in airway epithelial cells . However, this effect was demonstrated at a concentration of 1 µM simvastatin, while we applied concentrations in the nanomolar range as these are concentrations obtained in serum from patients receiving statin therapy .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, neither simvastatin nor TSA increased expression of LL‐37/hCAP‐18 in A549 cells investigated in our study. Statt et al observed a mevalonate‐dependent induction of CAMP gene expression by simvastatin in airway epithelial cells . However, this effect was demonstrated at a concentration of 1 µM simvastatin, while we applied concentrations in the nanomolar range as these are concentrations obtained in serum from patients receiving statin therapy .…”
Section: Discussionmentioning
confidence: 96%
“…A linkage between statins and the expression of the anti‐microbial peptide LL‐37/hCAP‐18 has previously been described in airway epithelial cells . In addition, pravastatin has been suggested to reduce the recurrence of urinary tract infections , but clinical data on the overall effect of statins on urinary tract infections are limited and inconsistent .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarah et al showed that prior exposure to physiological nanomolar serum concentrations of simvastatin confers significant cellular resistance to the cytotoxicity of pneumolysin, which revealed how statins contribute to the reduced pathology observed in the context of pneumonia and other bacterial infections [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet demonstrated in neutrophils or platelets, statins, specifically simvastatin, and also pravastatin, have been reported to protect both isolated human airway epithelial cells 151 and microvascular endothelial cells 152 against the cytotoxic actions of Ply. The latter study also documented a survival benefit of administration of simvastatin to pneumococcus infection-prone sickle-cell disease mice experimentally infected with the pathogen.…”
Section: Adjuvant Strategies Targeting Pneumolysinmentioning
confidence: 97%